Partial discharge signal pattern analysis from frequency spectrum - Lim Hong Tian (2023)
This thesis reports the Partial Discharge (PD) Signal Pattern Analysis Using Frequency Spectrum. The problem that may happen in high voltage power cable is the destruction or deterioration of the insulation. Internal partial discharges traced inside the insulation has been identified as one of the major contributor for the high voltage power cable failures. Many power utilities had employed PD measurement and PD test as a method of diagnosis for the high voltage power equipment. In order to understand the current situation, literature review on PD phenomena in power cable were carried out.